2005
DOI: 10.3748/wjg.v11.i48.7651
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriupregulates prion protein expression in gastric mucosa: A possible link to prion disease

Abstract: H pylori infection leads to the upregulation of gastric PrPc expression. This can be linked to H pylori induced hypergastrinemia and increased mucosal PGE(2) and IL-1beta synthesis. H pylori creates a milieu for enhanced propagation of prions in the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…In the S. Tm infected mice, PrP C expression was increased by 3-fold in the caecum and increased by approximately 1.5-fold in the draining MLN, consistent with increased PrP C expression detected in the stomach of humans with Helicobacter -induced gastritis [40]. Since PrP C expression directly correlates with incubation period, or the time from prion inoculation to development of terminal scrapie [41], the elevated PrP C expression in the caecum may lead to increased PrP conversion and accelerated prion transport and neuroinvasion.…”
Section: Discussionsupporting
confidence: 54%
“…In the S. Tm infected mice, PrP C expression was increased by 3-fold in the caecum and increased by approximately 1.5-fold in the draining MLN, consistent with increased PrP C expression detected in the stomach of humans with Helicobacter -induced gastritis [40]. Since PrP C expression directly correlates with incubation period, or the time from prion inoculation to development of terminal scrapie [41], the elevated PrP C expression in the caecum may lead to increased PrP conversion and accelerated prion transport and neuroinvasion.…”
Section: Discussionsupporting
confidence: 54%
“…Pammer et al (9) found that the expression of PrP C was negative or weak in the neck region of gastric mucosa but was up-regulated in the mucosa of patients infected with Helicobacter pylori (Hp). Recent work (10) confirmed the result and further proved that up-regulation of gastric PrP C expression by Hp infection was linked to Hp-induced hypergastrinemia. Since Hp infection is thought to play an important role in carcinogenesis of gastric mucosa, it is interesting to investigate the relationship between PrP C and gastric cancer.…”
mentioning
confidence: 55%
“…Role of PrP C in against oxidative stress and serum deprivation have also been intensively studied (5,6). In addition to the nervous system, PrP C is also expressed in the mucosa of gastrointestinal tract (23), especially in the case of Hp infection (10). Our previous studies showed that PrP C was overexpressed in gastric cancer tissues and correlated with tumor histological types and TNM stages (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Infection by Helicobacter pylori significantly upregulates PrP C expression, and may be an important factor in human susceptibility to infectious prions in contaminated food [45].…”
Section: Functional Dynamics and Environmental Vulnerability Of Prpmentioning
confidence: 99%